Phylogenetic Analysis and Antigenic Epitope Profiling of Glycoprotein E Gene of Bovine Herpesvirus-1 - Panwar, Diksha; Kumar, Aman; Singh, Neha; Sharma, Anubha; Maan, Sushila (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The current study focused on the characterization of the glycoprotein E (gE) gene of Bovine herpesvirus-1 (BoHV-1) isolates and the prediction of antigenic epitopes for peptide-based diagnostics or vaccines. The study utilized a BoHV-1 isolate (BoHV-1/ABT/LUVAS/ HSR/2016) stored in the department which was earlier isolated from vaginal swab of aborted buffalo. The nucleotide sequencing of the gE gene showed a partial length of 689 bp, exhibiting a 98-99.85% identity with BoHV-1.1 and 1.2 strains from Indian and global sequences available in GenBank database. Phylogenetic analysis clustered the BoHV-1 isolate with BoHV-1.1 and BoHV-1.2 strains. The deduced amino acid sequence revealed characteristic signal sequences, conserved cysteine residues, glycosylation site, and a substitution (L→H) at the 164th position, distinguishing it from other strains.Antigenic epitopes were predicted using various methods, including Kolaskar & Tongaonkar Antigenicity Prediction, Bepipred, ABCpred, and SVMTrip. In total 50 antigenic epitopes were predicted of which the Kolaskar & Tongaonkar method identified 21 antigenic peptides ranging from 6-21 amino acids in length within the 568-mer sequence. In conclusion, the present studyprovides valuable insights into the phylogenetic relation and peptide profiling of gE gene of BoHV-1. Moreover, this study enriches the knowledge related to gE which contributes to the prevention and control strategies against BoHV-1